Phenolic Profile of Seedless Ziziphus mauritiana Fruits and Leaves Extracts with In Vivo Antioxidant and Anti‐Inflammatory Activities: Influence on Pro‐Inflammatory Mediators - Arifa Khanam (22330756) (2024)
The present study aimed to assess the antioxidant and anti‐inflammatory activities of polyphenol‐rich extracts of seedless variety of Ziziphus mauritiana (SZM). Reverse Phase High Performance Liquid Chromatography (RP‐HPLC) analysis of SZM leaves and fruit extracts in ethanol revealed the presence of sixteen phenolics including chlorogenic acid, p‐coumeric acid, gallic acid, kaempferol, rutin and quercetin. Leaf extract showed higher total phenolic and total flavonoid contents (177.6 mg/100 g and 46.2 mg/100 g) than in fruit extract (137.8 mg/100 g and 14.1 mg/100 g). The leaf extract exhibited higher DPPH radical‐scavenging activity (63.5 %) than the fruit extract (58.2 %). The anti‐inflammatory activity was evaluated on carrageenan‐induced rat model and suppression of inflammatory biomarkers (Interleukin‐6, Tumor necrosis factor‐α and CRP) were studied. The fruit extract exhibited remarkable inhibition (98.1 %) at the dose level of 500 mg/kg body weight (BW), comparable to the standard drug indomethacin (98.4 %). Both extracts suppressed the inflammatory biomarkers and more pronounced results showed by the fruit extract including CRP, IL‐6, and TNF‐α. The leaf extract demonstrated the higher antioxidant potential as evident from the superoxide dismutase, catalase, malondialdehyde, glutathione peroxidase and glutathione levels. These findings suggest that SZM leaf and fruit extracts possess potential antioxidant and remarkable anti‐inflammatory properties and can play a significant role in mitigating oxidative stress. Other Information Published in: Chemistry & Biodiversity License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/cbdv.202401728